EssentialsPharmacology - Danielson, Jennifer (St. Paul ; Los Angeles : Paradigm Pub., 2011)
A new addition to Paradigm's Pharmacy Technician series, Pharmacology Essentials for Technicians covers the full range of pharmacology concepts at the need-to-know level. Four types of review exercises build student knowledge as well as critical thinking skills. Features: Content organized by body system; Provides a brief review of anatomy and physiology for each body system; Offers study tips correlated to the major learning styles; Presents health concerns, drugs, and additional treatments in table format for quick comprehension; Colorful illustrations, pill photos, and drug labels reinforce learning of drug facts; Developed on foundation of ASHP learning objectives. - Publisher.
Introduction. Studying pharmacology -- Drugs in the body -- Drugs for the immune system. The immune system and drugs for infectious diseases -- Immunologic drugs and vaccines -- Drugs for the integumentary and skeletal systems. The skin and dermatologic drug therapy -- The skeletal system and drug therapy -- Drugs for the nervous, muscular, and sensory systems. The nervous system and drug therapy -- Drugs for psychiatric and mood disorders -- Drugs for pain, headache, and anesthesia -- The muscular system and drug therapy -- Drugs for eyes, ears, nose, and throat -- Drugs for the cardiovascular and respiratory systems. The cardiovascular system and drug therapy -- The blood and drug therapy -- The respiratory system and drug therapy -- Drugs for the digestive and endocrine systems. The gastrointestinal system and drug therapy -- Nutrition and drugs for metabolism -- The endocrine system and drug therapy -- Drugs for the genitourinary system. The reproductive system and drug therapy -- The renal system and drug therapy -- Drugs for specialized therapies. Fluids and electrolytes -- Cancer and chemotherapy -- Appendices. The Pharmacists' Inventory of Learning Styles (PILS) Assessment -- Look-alike and sound-alike drug names.
Keywords: Pharmacology; Textbooks